2015
DOI: 10.1007/s12013-015-0694-5
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Promotes Cell Cycle Arrest and Inhibits Survival of Human Renal Cancer Cells by Negative Modulation of the PI3K/AKT Signaling Pathway

Abstract: Curcumin possesses anti-cancer effects. In the current study, we tested the effect of curcumin on cell proliferation, viability, apoptosis, cell cycle phases, and activation of the PI3K/Akt pathway in the renal cell carcinoma (RCC) cell line RCC-949. We observed that cell proliferation and viability were markedly inhibited by curcumin, while cell apoptosis was promoted. The latter effect was associated with increased expression of Bcl-2 and diminished expression of Bax (both: mRNA and protein). The cells treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 21 publications
3
21
0
Order By: Relevance
“…Treatment with curcumin inhibits the PI3K/AKT pathway in various types of cancer cells including breast cancer [17], lung cancer [18], colon cancer [19], renal cancer [20], ovarian carcinoma [21], pancreatic cancer [22], osteosarcoma [23], acute T cell leukemias [24], and liver cancer [25]. The results of this study are consistent with these reports.…”
Section: Discussionsupporting
confidence: 88%
“…Treatment with curcumin inhibits the PI3K/AKT pathway in various types of cancer cells including breast cancer [17], lung cancer [18], colon cancer [19], renal cancer [20], ovarian carcinoma [21], pancreatic cancer [22], osteosarcoma [23], acute T cell leukemias [24], and liver cancer [25]. The results of this study are consistent with these reports.…”
Section: Discussionsupporting
confidence: 88%
“…To the best of our knowledge, Akt/mTOR signaling pathway is one of the most important signaling pathways regulating apoptosis and cyclic protein of tumor cells. 31 , 32 Activated ERK1/2 could increase the production of MMPs. 33 As expected, LEF1-AS1 knockdown decreased the cell pro-invasion protein (MMP9 and MMP2), G1 phase protein (cyclinD1), and Blc-2 significantly in both U87 and U251 cell lines, while it decreased the cell-cycle regulatory protein p27 and pro-apoptosis protein Bax significantly, indicating that LEF1-AS1 -regulated GBM progression involved these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Across a variety of studies, curcumin has shown numerous pharmacological activities, including anti-inflammatory [ 92 , 93 , 94 ], antiviral [ 95 , 96 ], anti-oxidant [ 94 ], wound healing [ 97 ], hepatoprotective [ 98 ], and anti-microbial effects [ 99 , 100 ]. Moreover, curcumin has been used as a chemopreventive agent and an anti-cancer therapy in several human carcinomas, including colorectal [ 101 ], melanoma [ 102 ], lymphoma [ 103 ], breast [ 104 , 105 ], thyroid [ 106 ], head and neck [ 107 ], prostate [ 108 ], pancreatic [ 109 , 110 ], ovarian [ 111 ] and RCC [ 91 , 112 , 113 , 114 , 115 , 116 , 117 , 118 ].…”
Section: Natural Products and Renal Cell Carcinomamentioning
confidence: 99%
“…Woo et al, also suggested that curcumin induced apoptosis through the dephosphorylation of AKT, down-regulation of BCL-2, BCL-XL and inhibitor of apoptosis protein (IAP) proteins, activation of caspase 3 and release of cytochrome C [ 114 ]. Zhang and groups demonstrated that curcumin significantly inhibits proliferation of RRC-949 cell lines and induces cell apoptosis, possibly via regulation of BCL-2 and BAX, and initiates cell cycle arrest in G2/M phase [ 116 ]. Curcumin exposure induces apoptosis through cell cycle arrest in G1-phase and increases the volume of human kidney cells by modulating chloride ion channel [ 91 ].…”
Section: Natural Products and Renal Cell Carcinomamentioning
confidence: 99%